Separate aspects of criminology of setting of social works as alternative type of punishment - Потильчак, Анна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The article is devoted the problem of setting of social works as an alternative type of punishment imprisonment. In particular, the positive and negative sides of application of this type of punishment areprobed, and also blanks in a legislation, which touch setting of social works, are examined.